Alto OS Design Notes - Lampson, Butler (Xerox PARC memo, 1973)
This memo is a tentative specification of the operating system for Alto which Gene McDaniel is writing. Comments and suggestions are solicited. We begin by considering what features we will need in six months, and then try to find a subset with which to start. Stoy and Strachey’s OS6 system (Computer Journal, July and October 1972) is the source for a good deal of the terminology and some of the ideas.